TAFSIR BUDAYA ATAS TRADISI BARZANJI DAN MANAKIB - Ahmad Ta’rifin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2010)
Barzanji and Manakib, as an Islamic traditional culture in Java of Indonesia, has been observably detected in traditional muslim’s religious life. Reading Barzanji, is aimed to upgrade faith and love of Prophet Muhammad saw, whereas reading Manakib is tracing the miracle tale of Abdul Qadir Jaelani. These rituals have been constantly civilized among traditional Javanese muslims for centuries, even in local tradition of Kauman, Comal Pemalang. Using triple approaches (fenomenology, anthropology, and ethnography), this research was aimed to analyze the depth meaning of Barzanji and Manaqib tradition among Kaumaneese people, including their cultural shifting and its preservation.